2016
DOI: 10.3389/fneur.2016.00210
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage: Perihemorrhagic Edema and Secondary Hematoma Expansion: From Bench Work to Ongoing Controversies

Abstract: Intracerebral hemorrhage (ICH) is a medical emergency, which often leads to severe disability and death. ICH-related poor outcomes are due to primary injury causing structural damage and mass effect and secondary injury in the perihemorrhagic region over several days to weeks. Secondary injury after ICH can be due to hematoma expansion (HE) or a consequence of repair pathway along the continuum of neuroinflammation, neuronal death, and perihemorrhagic edema (PHE). This review article is focused on PHE and HE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 158 publications
(173 reference statements)
2
37
0
Order By: Relevance
“…Hence, it is quite prerequisite to analyze the possible risk factors that may lead to DHE so that physicians could take better treatment as early as possible in order to reduce the subsequent deterioration and improve patients' functional outcomes. Results from our patients in the DHE multifactor analysis study showed that initial hematoma volume and the effects of age are risk factors for DHE after sICH, concluding that the larger the initial hematoma volume, the more prone to DHE, which is in accordance with the results of previous studies . A recent review article detailed that a few days or weeks after sICH, the main cause of PHE is the release of hemoglobin degradation products after the red blood cells are dissolved; perhaps according to larger cerebral hemorrhage initial hematoma volume, the greater the toxicant secondary to the hemoglobin degradation more prone to cause the DHE .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, it is quite prerequisite to analyze the possible risk factors that may lead to DHE so that physicians could take better treatment as early as possible in order to reduce the subsequent deterioration and improve patients' functional outcomes. Results from our patients in the DHE multifactor analysis study showed that initial hematoma volume and the effects of age are risk factors for DHE after sICH, concluding that the larger the initial hematoma volume, the more prone to DHE, which is in accordance with the results of previous studies . A recent review article detailed that a few days or weeks after sICH, the main cause of PHE is the release of hemoglobin degradation products after the red blood cells are dissolved; perhaps according to larger cerebral hemorrhage initial hematoma volume, the greater the toxicant secondary to the hemoglobin degradation more prone to cause the DHE .…”
Section: Discussionsupporting
confidence: 90%
“…It is generally recognized that the disruption of vessels will rapidly cause a hematoma and vasogenic edema in the super‐acute stage of ICH. Except the hematoma occupying effect, the production of thrombin and activation of blood coagulation cascade contributes to a slow progressive edema growth, approximately peaking on the seventh day after ICH . On the other hand, the breakdown of the blood brain barrier, inflammatory cascades, heme, and iron load secondary to red cell dissolution as well as hemoglobin degradation will give rise to or accelerate PHE, but PHE will ameliorate or disappear with the alleviation of hematoma .…”
Section: Introductionmentioning
confidence: 99%
“…Following the onset of ICH, blood components enter the brain and activate resident microglia . Concomitant with subsequent leukocyte infiltration, activated microglia augment the local production of proinflammatory cytokines, which amplifies blood–brain barrier (BBB) disruption and accelerates the expansion of perihematomal edema (PHE), resulting in more severe and durable brain injury . Although emerging evidence has implicated inflammation as a major component of PHE in the acceleration of brain injury following hemorrhage, the action of brain‐intrinsic factors in injury‐induced neuroinflammation remains poorly defined in ICH …”
Section: Introductionmentioning
confidence: 99%
“…Considering the aging of populations, the incidence of ICH is expected to increase (van Asch et al, ). Currently, there is no effective therapy available to improve the clinical end points of ICH, because of the combined effect of primary injury and secondary damage (Fiorella, Zuckerman, Khan, Ganesh Kumar, & Mocco, ; Hemphill et al, ; Mittal & LacKamp, ). The primary injury is mainly caused by the mechanical oppression and destruction to the surrounding tissue by hematoma formation (Wang, ; Zheng, Chen, Zhang, & Hu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh Kumar, & Mocco, 2015;Hemphill et al, 2015;Mittal & LacKamp, 2016). The primary injury is mainly caused by the mechanical oppression and destruction to the surrounding tissue by hematoma formation (Wang, 2010;Zheng, Chen, Zhang, & Hu, 2016).…”
mentioning
confidence: 99%